Simulation and experimental investigation of swirl-loop scavenging in two-stroke diesel engine with two poppet valves. (June 2021) - Xu, Zheng; Ji, Fenzhu; Ding, Shuiting; Zhao, Yunhai; Wang, Yan; Zhang, Qi; Du, Farong; Zhou, Yu
Scavenging is becoming one of the determinants of two-stroke engine performance. Efficiency of U-type loop scavenging of two-stroke diesel engine with two poppet valves is generally unsatisfactory due to scavenging short-circuiting and large amount of residual burned gas in cylinder, and it is hard to generate the swirl that facilitates fuel spray mixing and combustion. In order to deal with the above issues, a swirl-loop scavenging configuration is proposed to involve swirl and depress short-circuiting. To investigate swirl-loop scavenging performance, this article simulates the scavenging process by numerical method, optimizes the tracer gas method to measure and evaluate the scavenging performance, as well as analyzes the influence factors. The results demonstrate that, compared with U-type loop scavenging, the trapping efficiency and scavenging efficiency of swirl-loop scavenging respectively increase by 8% and 10%. Change of engine speed has an impact on the delivery ratio and trapping efficiency but load does not. Both intake and exhaust valve timings affect scavenging performance and short-circuiting to a large extent. In addition, the accuracy of tracer gas method in measurement of scavenging performance parameters is improved, and the scavenging efficiency deviation between simulation and experiment is decreased from 6% to 2%.